Rekonstrukce objektu na penzion s restaurací - Halama, Stanislav (Vysoké učení technické v Brně. Fakulta stavební, 2014)
V projektu je zpracována kompletní dokumentace rekonstrukce objektu na penzion s restaurací na úrovni zadání projektu pro stavební povolení. Návrh objektu klade důraz na dispoziční řešení s vazbou na zajištění konstrukce po stránce statické, požární bezpečnosti, ochrany proti hluku, úspory energie a bezpečnosti při užívání. Výkresy byly zpracovány v softwaru určeném pro projektování – Autocad.

The project is working on a complete documentation of Reconstruction of the building to the boarding with restaurant at the project specification for a building permit. Proposal places emphasis on building layout with a link to the site to ensure construction of static, fire safety, protection against noise, energy saving and safety in use. Drawings have been processed in software for design – Autocad.
Reconstruction of the building to the boarding with restaurant
Keywords: Rekonstrukce objektu na penzion s restaurací; diplomová práce.; Reconstruction of the building to the boarding with restaurant; masters thesis.